Comportamiento de diferentes cultivares de trigo a Wheat streak mosaic virus (WSMV) y High Plains virus (HPV) mediante infección artificial con el vector Aceria tosichella Keifer, bajo condiciones de campo (RIA: Revista Investigaciones Agropecuarias, 2013)
Wheat (Triticum aestivum L.) is the most economically important winter cereal in Argentina. Its production is limited by several factors, including viral diseases. Since Wheat streak mosaic virus (WSMV) and High Plains virus (HPV) are one of the main limitations i wheat production, the aim of this study was to evaluate the behavior of different wheat genotypes in artificial infections with both pathogens under field conditions. HPV-WSMV mixed inoculums and the vector Aceria tosichella were obtained from field sampling and multiplied in wheat under laboratory conditions. These HPV-WSMV infected eriophyid were used to perform artificial infections inthe field. Incidence and symptoms severity levels were evaluated in different wheat cultivars. Genotypes were classified by the probability of incidence of both viruses showing significant differences only in infections with HPV. No significant differences were found in the susceptibility of cultivars to WSMV. Mixed infections were observed only in 9.2 % of wheat genotypes analyzed. Mild to moderate symptoms were shown by infected plants.These results are a potential tool for the selection of best performing genotypes in this productive context.